Hibridações locais e processos identitários: o Rap em Goiânia e Aparecida de Goiânia - Magalhães , Maria Cristina Prado Fleury (2015)
This dissertation resulted from a research that aimed to investigate the rap produced in Goiânia, focusing on its hybrid origins in dialogue with regional cultural aspects, aiming to reach identity processes built through this practice. As street culture that includes in its four constitutive elements (DJ, MC, graffiti and break) different forms of expression (music, poetry, visual arts and dance), the hip hop stands as a movement that articulates four fields of artistic production, being able to communicate by different manifestations which are imbricated and share the same ideology. The union of two of the elements from hip hop movement (DJ and MC) compose the rap, musical style chosen as research subject. Since rap shows remaining features from several cultural practices that are imbricated in their configuration as expression that hybridizes, mainly, elements from Caribbean, Africa and North America, this work is supported by the following analisys categories: cutural identity set by Hall (2006), cultural hybridity, developed by García Canclini (2003) and by Burke (2003) and struggles for meaning, approached by Chartier (1990) and Bourdieu (2011). The present dissertation brings up, first, a history of the organization of the ghettos and the US Black movement, highlighting how genres of African-American music like soul and funk relate to this context and with the appearance of rap. Then it approaches the rap in its genesis, cultural matrices and constitutive elements, and its insertion in hip-hop culture. Afterward, it draws a brief history of the spread of rap through the music industry and hybridization processes resulting in different genre styles, including in Brazil. Then it addresses the arrival of rap in Goiânia, its historical trajectory and current scenario. Finally, it investigated (through rap music analysis on phonographic records and freestyle battles) the identity representations found in rap of Goiânia and of Aparecida de Goiânia, from the finding of hybridization of local elements and struggles for meaning in these musical practices. It was found that Goiânia rap groups elected stereotypical elements of the local culture as the viola, the catira dance and the accent to represent the Goiás identity in its compositions. The analysis revealed that the rap battles of Goiânia and Aparecida de Goiânia stand as struggles for meaning in which groups are represented through symbolic disputes. This work also concluded that rap acts as a mediator of power representations experienced by young people living in peripheric regions of Goiânia and Aparecida de Goiânia. The representation elements are used to stake out and enhance the differences and boundaries between two neighbourhoods. However, in a broader view, the groups show similarities expressed by appreciation of the Goiás identity, by the declaration of Black pride and by the feeling of belonging to a marginalized urban territory and a socially excluded group.